1992
DOI: 10.1177/019459989210600131
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Sensorineural Hearing Loss in Treated Infants and Children with Congenital Toxoplasmosis

Abstract: Educationally significant hearing loss has been reported in 10% to 15% of children with congenital toxoplasmosis. As part of a pilot study to assess feasibility and safety of prolonged therapy for congenital toxoplasmosis, 30 congenitally infected infants and children were evaluated for auditory function. Serial testing, beginning within 2 months of birth, was performed. Availability of auditory brainstem response (ABR) testing made evaluation at an earlier age than previously possible. Six (20%) of the 30 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
3
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 7 publications
1
35
3
2
Order By: Relevance
“…In the present study, proper treatment of two of these children with hearing loss did not help avoid the loss, and this is different from the results attained by McGee et al 15 and McLeod et al 20 who reported hearing normality in treated children, even when they had neurologic and ocular involvement. The follow up of these children may provide new data to clarify these issues.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In the present study, proper treatment of two of these children with hearing loss did not help avoid the loss, and this is different from the results attained by McGee et al 15 and McLeod et al 20 who reported hearing normality in treated children, even when they had neurologic and ocular involvement. The follow up of these children may provide new data to clarify these issues.…”
Section: Discussioncontrasting
confidence: 99%
“…Table 5 shows comparisons of three studies which encompassed hearing evaluation in children with congenital toxoplasmosis. The Chicago Study 15,20 evaluated children treated with the classical antiparasitic drugs for 12 The results observed in this study are similar to those found by Wilson et al 19 Studies with larger samples, submitted to long stand treatment (12 months), did not identify the presence of hypoacusis, concluding for a better prognosis of the treated children 20 . In the present investigation, among the 16 children properly treated, for long time and regularly, two presented hearing deficit, but only one had an important functional loss.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations